(untitled) (Research, Society and Development, 2023)
Chronic Noncommunicable Diseases (NCD) are a group of diseases with multifactorial causes, which interact with each other, with a higher prevalence of death worldwide. It is important to include healthy and adequate habits for prevention, since a relationship between these diseases and these factors is evident. The objective of this study was to identify the importance of healthy and adequate habits in the prevention of NCD and thus enable greater longevity with quality of life. The present study consists of an integrative exploratory literature review, through electronic searches in the Virtual Health Library (VHL), Scientif Electronic Library Online (SciELO), National Library of Medicine (PubMed), Google Scholar databases. The descriptors used were chronic diseases, healthy habits, physical activity, quality of life, disease prevention. Inclusion criteria were limited to articles published in the last 05 years (2018 to 2022). Twenty articles were selected. The results of the selected articles were evaluated and arranged in a comparative table. In these studies, an increase in the prevalence of CNCDs is observed in people of different age groups and socioeconomic status associated with inadequate lifestyle habits. Thus, they reinforce the importance of raising awareness about the need to preventively include healthy and appropriate habits in the daily lives of people with chronic diseases and also the promotion of this practice in society. Therefore, it is possible to highlight the importance of healthy and adequate habits for the prevention of CNCD and their relationship with the habits and lifestyles of carriers and their quality of life.